Pengaruh Penyemprotan Larutan Asam Hipoklorit (HOCl) dengan Konsentrasi dan Durasi Berbeda terhadap Stabilitas Dimensi Hasil Cetakan Alginat - Prajogo, Johanna Kezia; Fulyani, Faizah; Purnomo, Brigitta Natania Renata; Santoso, Oedijani (Acta Odontologica Indonesia, 2025)
Background: Disinfection of alginate impressions is performed to prevent cross-infection. Alginate possesses properties of imbibition and syneresis which affect the dimensional stability of the impression. The disinfectant solution, hypochlorous acid (HOCl), is non-toxic, non-irritating, and non-corrosive at the appropriate concentrations. Hypochlorous acid has higher antimicrobial activity than sodium hypochlorite (NaOCl). Objective: This study aimed to determine the effect of spraying 0.01% and 0.02% HOCl with contact durations of 1 and 5 minutes on the dimensional stability of alginate impressions. Methods: This was a laboratory experimental study with a Post-Test Only Control Group Design. A total of 24 samples were divided into 4 treatment groups and 2 control groups. The dimensional stability of the alginate impressions was assessed by the difference in anteroposterior and mediolateral dimension measurements between the master model and the resulting gypsum casts, using a digital caliper. Measurements were taken 3 times by 3 different observers, followed by a two-way ANOVA statistical test. Results: The results of the two-way ANOVA test showed no significant difference between the groups with variations in concentration or contact duration. The largest dimensional difference was found in the control group sprayed with 5.25% NaOCl. Conclusion: Spraying alginate impressions with 0.01% and 0.02% HOCl with contact durations of 1 and 5 minutes does not affect the dimensional stability of the alginate impressions.